2009
DOI: 10.1002/jssc.200800567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of indole‐based probes for high‐throughput screening of drug binding to human serum albumin: Analysis by high‐performance affinity chromatography

Abstract: There has been growing interest in the use of rapid and selective separation methods such as highperformance affinity chromatography (HPAC) or affinity capillary electrophoresis (ACE) for the characterization of drug-protein interactions. L-Tryptophan is commonly used in these and other methods as a site-selective probe for examining the binding of small solutes and drugs at Sudlow site II on the protein human serum albumin (HSA). However, solutions of L-tryptophan can be unstable and are generally prepared fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 42 publications
1
54
0
Order By: Relevance
“…The glimepiride, tamoxifen, digitoxin, racemic warfarin, and R- warfarin solutions were used within two weeks of preparation [8,58,61]. Previous studies have shown that solutions of L-tryptophan in pH 7.4 phosphate buffer are only stable for a period of 2–9 days, so these solutions were prepared and used within one day of preparation [8,61,62]. …”
Section: Methodsmentioning
confidence: 99%
“…The glimepiride, tamoxifen, digitoxin, racemic warfarin, and R- warfarin solutions were used within two weeks of preparation [8,58,61]. Previous studies have shown that solutions of L-tryptophan in pH 7.4 phosphate buffer are only stable for a period of 2–9 days, so these solutions were prepared and used within one day of preparation [8,61,62]. …”
Section: Methodsmentioning
confidence: 99%
“…It is known to contain two major binding sites for the majority of drugs, namely Sudlow site I (also often called the warfarin-binding site)56 and Sudlow site II (also often called the benzodiazepine site)57 (Figure 2E). Sudlow site I, located in subdomain IIA, is a big hydrophobic cavity where interactive associations of drugs bind 55.…”
Section: Discussionmentioning
confidence: 99%
“…All solutions and samples containing R- warfarin were used within two weeks of preparation to ensure stable conditions for drug-protein binding measurements [21,22,38]. The L-tryptophan solutions were prepared fresh daily in the same pH 7.4 buffer, as described previously [21,22,39]. These samples were applied or injected at a typical flow rate of 0.50 mL/min, as shown in earlier studies to provide reproducible retention factors and binding capacities for these drugs and related solutes on similar HSA columns [10,18,21,22].…”
Section: Methodsmentioning
confidence: 99%